PENGARUH MARKET ORIENTATION, KNOWLEDGE MANAGEMENT, DAN CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP BUSINESS PERFORMANCE - AULIA DANIBRATA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2014)
The purpose of this study was to examine the influence market orientation, knowledge management, dan customer relationship management toward business performance. The research sample was 100 respondents selected by random sampling method from saving’s customer several state owned banks within Jakarta. Data analysis method used is multiple regression analysis. The result on this research is there an effect market orientation, knowledge management, and customer relationship management toward business performance. It’s mean that all the independent variables are have effect toward dependent variable.